Modern Technology Microphone Face Mask - Singh, Gourav (Journal of Advanced Research in Information Technology, Systems and Management; Vol 7 No 2 (2023): Journal of Advanced Research in Information Technology, Systems and Management, 2023)
We have come across so many diseases from our early age. During every such occurrence, mankind fought for their survival using various developments to handle, resist and overcome the spread of disease. In this current situation the world is suffering from COVID-19. One of the major pre-cautions to stop spreading the SARS COV-2 is to wear a mask that plays a major role to stop spreading virus from one person to another person. Currently we have many types of masks in use such as surgical mask, cloth mask, N95 respirator mask etc. An elaborate literature review of all the masks is given. The proposed method is to introduce a new microphone face mask which can be used in operation theatre, educational purpose and in important bases. The face mask contains an air filter which has an elegant feature and it has no contact with the face area. It has a transparent adjustable face shield that covers the face along with the microphone.